Milly, Molly and the Mountain - Pittar, Gill (Milly Molly Books, 2002)
The Milly, Molly series of books are stories about values, and have been written to promote the acceptance of diversity and sound values for character education.
Keywords: Juvenile literature-English language-Fiction